Virtues, Psychological Distress, and Resilience among Adolescents - Ardra Dileep; annalakshmi, Narayanan (Asia Pacific Journal of Social Science Research, 2022)
The present study examines the relationship between virtues on one hand and psychological distress and resilience on the other hand. The study participants include 163 students from class seventh to twelfth, in the age group 12-17 years studying in government schools. The self-reported measures used for collecting data include the VIA youth-96 survey, depression anxiety stress scale and Bharathiar University resilience scale. ANOVA and multiple regression were used for the analysis.  No gender difference in justice, temperance, wisdom, courage, humanity, psychological distress, and resilience was found. The females were significantly higher than males on transcendence and courage. There is no significant difference between areas of residence in justice, temperance, transcendence, wisdom, courage, psychological distress, and resilience. Those from rural areas were higher on humanity than those from a small town. Temperance negatively predicted psychological distress, while wisdom positively predicted psychological distress. It is intriguing to note that none of the six virtues predicted resilience. The findings are discussed with implications for future research, practice, and policy.